Difference planted season and creeper-pole on both growth and yield of the two cultivars of velvet bean (Mucuna pruriens (L.) DC.) - SUPRIYONO SUPRIYONO (Society for Indonesian Biodiversity, 2008)
The aims of this research were to know the effect of different cultivars, planted seasons and creeper poles at velvet bean (Mucuna pruriens (L.) DC.) growth, yield and their interactions. This research was conducted on litosol soil in Tancep, Ngawen, Gunungkidul on 170 m up sea level and 9-10Â° elevation. The depth of soil tillage was 5-17 cm. Design utilization was Randomized Completed Block Design (RCBD) with factorial 3 factors. The treatment was (i) cultivars: rase and putih Gunungkidul (ii) planted seasons: dry and rainy seasons and (iii) creeperpoles: control, corn 0 weeks old, corn 2 weeks old, corn 4 weeks old and bambu. There is replicated 3 times. The result of this research was the 1st velvet bean growth on rainy season was rapidly but they have long time planted. The 2nd, by splited rase cultivars, rainy season and creeper-pole utilization was yield increased. The 3rd, on the rainy season, the high yield was come by rase cultivar and creeper-poleutilization. The 4th, with the 2 times velvet bean density and without calculated corn yield, rase cultivar planted on rainy season and bamboo creeper-pole coused the highest velvet bean yield but no significant different with 4 weeks corn creeper-pole.Â© 2008 Jurusan Biologi FMIPA UNS Surakarta.Key words: cultivars, planted seasons, creeper-pole, velvet bean (Mucuna pruriens (L.) DC.).